Diminishing the self-stigma of mental illness by coming out proud. Issue 1 (30th September 2015) - Corrigan, Patrick W.; Larson, Jonathon E.; Michaels, Patrick J.; Buchholz, Blythe A.; Rossi, Rachel Del; Fontecchio, Malia Javier; Castro, David; Gause, Michael; Krzyżanowski, Richard; Rüsch, Nicolas
Abstract: This randomized controlled trial examined the impact of the Coming Out Proud (COP) program on self-stigma, stigma stress, and depression. Research participants who experienced mental health challenges were randomly assigned to a three session COP program ( n =51) or a waitlist control ( n =75). Outcome measures that assessed the progressively harmful stages of self-stigma, stigma stress appraisals, and depression were administered at pre-test, post-test, and one-month follow-up. People completing COP showed significant improvement at post-test and follow-up in the more harmful aspects of self-stigma compared to the control group. COP participants also showed improvements in stigma stress appraisals. Women participating in COP showed significant post-test and follow-up reductions in depression after COP compared to the control group. Men did not show this effect. Future research should determine whether these benefits also enhance attitudes related to recovery, empowerment, and self-determination. Highlights: Completing COP reduced self-stigma compared to the controls. COP participants showed improvements in stigma stress appraisals. Women showed significant reductions in depression after program completion.